Post-Traumatic Sarcomas: Do They Exist?. (October 2019) - Montgomery, Corey; Park, Kwan J.; Gardner, Jerad M.; Majors, Issac; Nicholas, Richard
Patients often cite a history of trauma prior to the diagnosis of a sarcoma. Sparse literature suggests that there may be a link between sarcoma development and trauma. A 10-year review of academic tertiary-referral sarcoma center database was examined to identify patients who developed a sarcoma after having a history of a significant musculoskeletal trauma. A total of 501 patients were treated for a sarcoma during this time period. Six patients were identified as previously having a significant musculoskeletal trauma at the site of sarcoma development. Half of the sarcomas arose in bone and the other half in soft tissue. Five (83%) patients had multiple operations for the injury with 3 (50%) patients having a postoperative wound infection. The average time from injury to development of the sarcoma was 19.8 years. Survival after diagnosis was poor, and 4 (67%) of the patients died due to their metastatic disease within 3 years of diagnosis. Our findings suggest the possibility of post-traumatic sarcomas.